Gender Differences in Financial Well-Being: A Multi-Group Analysis of Indonesian Income-Earning Gen-Z - Sutejo, Bertha Silvia; Wijaya, Liliana Inggrit; Noordin, Noorliza MD; Oktavianus, Joshua (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2026)
Gen-Z in Indonesia faces financial challenges due to low financial literacy, impulsive spending, and FOMO, prioritizing short-term desires over long-term financial freedom and stability. This study examines key determinants of financial well-being among Gen-Z, integrating gender differences as a moderator. Through PLS-SEM and MGA analysis of 612 respondents, this study identifies financial literacy, self-control, behavior, and stress as key determinants of financial well-being. Financial behavior and stress mediate key relationships, with gender differences in financial understanding and stress management. This study suggests that governments should introduce financial literacy earlier and offer accessible financial consultations, while Gen-Z must cultivate self-discipline and financial knowledge to achieve sustainable financial well-being.